Homeport [compact disc, unabridged] - Roberts, Nora (Brilliance Audio, 2008)
Dr. Miranda Jones is attacked outside her Maine home as she returns from a busy lecture tour. Determined to put the assault out of her mind, she welcomes the distraction offered by a summons to Italy to verify the authenticity of a Renaissance bronze of a Medici courtesan known as the Dark Lady. However, it nearly destroys her reputation when it is declared a hoax.